The electrical conductivity and microstructure properties of Ni-doped TiO2 ceramic - Yakuphanoglu, F.; Okutan, M.; Korkmaz, K. (Elsevier Science Sa, 2008)
The electrical, microstructure and crystal structure properties of Ni-doped TiO2 were investigated. The microstructure and crystal structure of Ni-doped TiO2 were analyzed by the scanning electron microscopy and X-ray diffraction techniques. The alternating conductivity (AC) and direct current conductivity (DC) properties of Ni-doped TiO2 have been investigated. DC conductivity exhibits a semiconductor behavior with the temperature. AC and DC measurements suggest that variable-range hopping (VRH) conduction is dominated by hopping of carriers between localized states at lower temperatures. At higher temperatures, the conduction mechanism of the sample is constant-range hopping charge transport. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: semiconductor; TiO2; conduction mechanism